FUTURE PSYCHOLOGISTS EXPERIENCING THE CRISIS OF PROFESSIONAL SELF-DETERMINATION: FEATURES OF MOTIVATIONAL SPHERE - Zlata Rzhevska-Shtefan (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The paper is aimed at identifying the features of the future psychologists' professional learning motivation under the conditions of experiencing the crisis of professional self-determination on the border of the 3rd and 4th year of study. The research was held at the Faculty of Psychology and Pedagogy of Volodymyr Vynnychenko Central Ukrainian State Pedagogical University during the years 2017-2018 and involved 47 3rd year and 63 4th year psychology students. The following methods were used: psychodiagnostic techniques "Motivation to study at a higher education institution" by Ilyina and "Personality orientation" by Bas. The data was compared to similar research conducted in the years 2003-2004. The study showed that the psychology students of recent years show more acute signs of experiencing the crisis of professional self-determination and the features of their motivational sphere could be characterised as mostly negative. The characteristic feature of the 3rd year students is high indicators of external motivation: egoistic "self-orientation" combined with dominating motives to obtain a diploma. For the 4th year students, the general decrease in motivation is combined with a trend of cognitive motivation decline. This tendency is mainly typical for the group of students who show an unwillingness to change the decision once made in relation to their choice of profession in spite of having negative attitude thereto. The accumulation of negative trends was interpreted in terms of the eco-facilitation approach as a forthcoming adaptive reaction of the eco-system.